1987
DOI: 10.1002/jcb.240350103
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐induced lysosomal proteases secreted by breast cancer cells: A role in carcinogenesis?

Abstract: In an attempt to understand the mechanism by which estrogens stimulate cell proliferation and mammary carcinogenesis, metastatic human breast cancer cell lines (MCF7, ZR75-1) were found to secrete a 52,000 dalton (52K) protein under estrogen stimulation. Following its purification to homogeneity, the 52K protein was identified as a secreted procathepsin-D-like aspartyl protease bearing mannose-6-phosphate signals. This precursor displays an in vitro autocrine mitogenic activity on estrogen-deprived MCF7 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
71
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 192 publications
(74 citation statements)
references
References 39 publications
0
71
0
3
Order By: Relevance
“…The lysosomal aspartyl proteinase, cathepsin-D (cath-D), is over-expressed and hyper-secreted by carcinoma cells (Rochefort et al, 1987). Many independent clinical studies have shown that the cath-D level in primary breast cancer cytosol is an independent prognostic parameter correlated with the incidence of clinical metastasis and shorter survival (reviewed by Rochefort, 1992;Ferrandina et al, 1997;Foekens et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The lysosomal aspartyl proteinase, cathepsin-D (cath-D), is over-expressed and hyper-secreted by carcinoma cells (Rochefort et al, 1987). Many independent clinical studies have shown that the cath-D level in primary breast cancer cytosol is an independent prognostic parameter correlated with the incidence of clinical metastasis and shorter survival (reviewed by Rochefort, 1992;Ferrandina et al, 1997;Foekens et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Like proteases acting at a neutral pH, such as the plasminogen activator and the matrix metalloproteinases, the precursors of lysosomal proteases (e.g. procathepsin-B, D, and L) are also over-expressed and hyper-secreted by carcinoma cells (Sloane and Honn, 1984;Rochefort et al, 1987;Kane and Gottesman, 1990). However, activation of these proteases requires an acidic pH which is rather found intra-cellularly in endosomes, lysosomes or phagosomes.…”
Section: Introductionmentioning
confidence: 99%
“…20 Conversely, it is secreted constitutively in ER À cell lines. 21 The mechanism of regulation of expression has been studied extensively and DNA sequences responsible for this regulation have been determined. 19,22 A strong predictive value was found for CD concentrations in breast cancer as well as many other tumor types.…”
mentioning
confidence: 99%